Global Climate Risk Index 2021: Who Suffers Most from Extreme Weather Events? - Eckstein, David; Kunzel, Vera; Shafer, Laura (German Watch, 2021)

Ed-Tech Within Limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ?greening? of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ?abundant? forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ?Ed-Tech Within Limits? might be pursued ? outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.

Ed-tech within limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ‘greening’ of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ‘abundant’ forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ‘Ed-Tech Within Limits’ might be pursued – outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen